Supercritical fluid chromatography for lipid analysis in foodstuffs. Issue 1 (9th November 2016) - Donato, Paola; Inferrera, Veronica; Sciarrone, Danilo; Mondello, Luigi
Abstract : The task of lipid analysis has always challenged separation scientists, and new techniques in chromatography were often developed for the separation of lipids; however, no single technique or methodology is yet capable of affording a comprehensive screening of all lipid species and classes. This review acquaints the role of supercritical fluid chromatography within the field of lipid analysis, from the early developed capillary separations based on pure CO2, to the most recent techniques employing packed columns under subcritical conditions, including the niche multidimensional techniques using supercritical fluids in at least one of the separation dimensions. A short history of supercritical fluid chromatography will be introduced first, from its early popularity in the late 1980s, to the sudden fall and oblivion until the last decade, experiencing a regain of interest within the chromatographic community. Afterwards, the subject of lipid nomenclature and classification will be briefly dealt with, before discussing the main applications of supercritical fluid chromatography for food analysis, according to the specific class of lipids.